Menakar Legalitas Pernikahan Dini (Dalam Perspektif Fiqh dan UU. No. 16 Tahun 2019 pasal 1) - Abdul Azis (Journal on Education, 2022)
Early marriage is not a new phenomenon, but a social phenomenon that is common in all places, both in Indonesia and in other countries. In the era of globalization, especially in Indonesia, data on early marriage have surfaced a lot. Pros and cons also emerged, including from the National Commission for Child Protection. Komnas Perempuan noted that in 2019 there were 23,126 early marriages, in 2020 there were 64,211, and in 2021 there were 59,709 cases of child marriage. Regarding early marriage, Indonesia is ranked 2nd in ASSEAN and is ranked 8th in the world for cases of child marriage. This research is a literary qualitative research in describing the reflections on fiqh and UU no 116 of 2019.